(untitled) (Research, Society and Development, 2021)
In view of the pandemic period brought about by the coronavirus (SARS-CoV-2) that causes the infectious disease known as COVID-19, the need arose to discuss alternatives to reduce the impacts on the population’s health and quality of life, with exercise and activity as a crucial tool for the maintenance, enhancement and promotion of health in the context of a pandemic. Thus, this research work presents the impacts associated with Activity and Physical Exercise in difficult times, such as the period of social isolation, bringing a holistic view to society’s health and quality of life. Thus, this literature review aims to present and analyze the relevance of Physical Exercise and Physical Activity in the midst of the COVID-19 pandemic, addressing care and benefits for human beings, linking the health and quality of life of the individual in the context Social. In this study we will also discuss the applicability relationship and the importance of the guidance of a Physical Education professional, respecting the guidelines for the best and safest application of Physical Exercises for each audience. The methodology used was bibliographic research, with a descriptive approach, based on books and articles already published, found in the database of the websites PubMed, Portal Periodical Capes, Google Academic and Scielo. The results show that through physical exercise it is possible to measure how fundamental this practice is to maintain the health and quality of life of individuals in society, in a delicate moment such as the pandemic, which changed the population’s life routine, as well as brought to light the understanding of the benefits that physical activities promote in the human being’s life.